2018
DOI: 10.1111/cen.13538
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda thyroid categories and family history of thyroid disease

Abstract: Family history plays a significant role in the development of thyroid cancer, and having first-degree relatives with not only medullary, but also papillary thyroid cancer strongly predicts the risk of developing the malignant thyroid disease. In contrast, benign thyroid disorders in family history do not lead to the development of thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Although controversial, the use of statins suggests that these patients already have an increased CVR. Even though, in one study, 34 the authors demonstrated that each 10% reduction in LDL-C was estimated to reduce IMT by 0.73% per year (95% CI, 0.27 to 1.19), the use of statins was not sufficient to prevent the reclassification to a higher cardiovascular risk group in our population of patients with asymptomatic T2DM. However, it is important to note that only 40.3% of patients were within the recommended LDL goal for high-risk patients according to the current Brazilian Cardiovascular Risk Prevention guidelines.…”
Section: Overview Of Demographic and Laboratory Data Of The Studied Pmentioning
confidence: 61%
See 4 more Smart Citations
“…Although controversial, the use of statins suggests that these patients already have an increased CVR. Even though, in one study, 34 the authors demonstrated that each 10% reduction in LDL-C was estimated to reduce IMT by 0.73% per year (95% CI, 0.27 to 1.19), the use of statins was not sufficient to prevent the reclassification to a higher cardiovascular risk group in our population of patients with asymptomatic T2DM. However, it is important to note that only 40.3% of patients were within the recommended LDL goal for high-risk patients according to the current Brazilian Cardiovascular Risk Prevention guidelines.…”
Section: Overview Of Demographic and Laboratory Data Of The Studied Pmentioning
confidence: 61%
“…In this condition, FH of thyroid disease is also considered a risk factor for familial tumors and may account for 5% to 15% of the cases. 34 In spite of that, it is important to emphasize that both FH of CHD and FH of thyroid disease were self-reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations